Albania : Access to Finance for Enterprise Sector - World Bank (World Bank, Washington, DC, 2012)
This report was prepared in close collaboration with the Bank of Albania. This report focused on trade, services, and agriculture; however, the limited scope of their operations still leaves a potentially large unmet demand for credit in agriculture. This report focuses on problems related to the operation of Immovable Property Registry System (IPRS) and other institutions and the formalization of property rights and inscription of mortgages. This study believes the reform with most optimum impact on sustainable credit growth will be focused on (i) improving the quality, breadth, and depth of financial intermediation, (ii) growth and development of credit unions and microfinance institutions, and (iii) facilitate the development of new instruments. The authorities will also focus on implementing reforms to become compliant with Financial Action Task Force (FATF) recommendation.